2020
DOI: 10.1038/s41598-020-71503-y
|View full text |Cite
|
Sign up to set email alerts
|

Serological cytokine signature in paediatric patients with inflammatory bowel disease impacts diagnosis

Abstract: Endoscopy is a central tool for diagnosing and evaluating paediatric inflammatory bowel diseases (PIBD), but is too invasive to be frequently repeated in young children. Furthermore, it is challenging to distinguish Crohn’s disease (CD) from ulcerative colitis (UC) endoscopically. This study aimed to determine biomarkers useful for the diagnosis of PIBD. Cytokines, chemokines, and growth factors were quantified in the sera of 15 patients with CD or UC, at disease onset prior to treatment, and 26 age-matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Also growth-regulated oncogene and TNF-α were higher in UC than in controls. This study observed clear differences in cytokine profiles between CD and UC, with IL-7 alone having the highest diagnostic accuracy [36].…”
Section: Biomarkers From Gut Microbiotamentioning
confidence: 63%
“…Also growth-regulated oncogene and TNF-α were higher in UC than in controls. This study observed clear differences in cytokine profiles between CD and UC, with IL-7 alone having the highest diagnostic accuracy [36].…”
Section: Biomarkers From Gut Microbiotamentioning
confidence: 63%
“…As described above, the cytokines present in saliva are the most extensively analyzed marker, although other analytes such as calprotectin, exosome-containing molecules, IgA, cortisol, amylase, and oxidative stress indicators have been proposed as indicators of the pathology status. Of the salivary components analyzed, IL-6 has the most interleukins studied, and the results are in accordance with an increase in its amount in the saliva both [ 21 , 36 , 37 , 38 , 47 ] in patients with CD and UC, whereas contradictory results have been observed for salivary TNF-α [ 21 , 36 ], circulating IL-6, and TNF-α, which are commonly used as indicators of disease activity in IBD and the state of endoscopic disease activity in IBD [ 88 , 89 ]. The key role of IL-6 in IBD is highlighted by the fact that the serum concentrations are directly correlated to the inflammatory disease activity.…”
Section: Discussionmentioning
confidence: 85%
“…Flow cytometric based assays can also be done with intracellular protein expression looking for deficiencies in FOXP3 leading to IPEX and XIAP especially in male patients (61,62). If available, cytokine and chemokine panels (IL-1, IL-2, IL-6, IL-10, IL-18, TNF-alpha, IFN-gamma) can be used to identify specific pathway defects, target treatment, and detect complications such as HLH development in XIAP (63,64). Endoscopy with histologic evaluation via hematoxylin and eosin (H+E) stain aids in the diagnosis of VEO-IBD though lacks diagnostic specificity.…”
Section: Discussionmentioning
confidence: 99%